2016
DOI: 10.1007/s10539-016-9533-3
|View full text |Cite
|
Sign up to set email alerts
|

The ontology of organisms: Mechanistic modules or patterned processes?

Abstract: Though the realm of biology has long been under the philosophical rule of the mechanistic magisterium, recent years have seen a surprisingly steady rise in the usurping prowess of process ontology. According to its proponents, theoretical advances in the contemporary science of evo-devo have afforded that ontology a particularly powerful claim to the throne: in that increasingly empirically confirmed discipline, emergently autonomous, higher-order entities are the reigning explanantia. If we are to accept the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 83 publications
(86 reference statements)
0
6
0
Order By: Relevance
“…In this paper, we have shown the utility of approaching pressing biological questions by appealing to metaphysical notions. Our approach follows a growing tendency in contemporary biological and philosophical research that consists in combining scientific practice with the use of the metaphysical discourse to clarify some scientific debates (Boogerd et al, 2005;Dupré, 2012Dupré, , 2015Mumford and Tugby, 2013;Guay and Pradeu, 2014;Austin, 2016Austin, , 2017Waters, 2017;Austin and Nuño de la Rosa, 2018;Nicholson and Dupré, 2018;Laplane et al, 2019;Triviño, 2019). Concretely, we have shown how approaching the concept of holobiont adaptation by appealing to the notions of emergence and inter-identity allows to shed light on some of the perceived issues in contemporary hologenome literature.…”
Section: Resultsmentioning
confidence: 99%
“…In this paper, we have shown the utility of approaching pressing biological questions by appealing to metaphysical notions. Our approach follows a growing tendency in contemporary biological and philosophical research that consists in combining scientific practice with the use of the metaphysical discourse to clarify some scientific debates (Boogerd et al, 2005;Dupré, 2012Dupré, , 2015Mumford and Tugby, 2013;Guay and Pradeu, 2014;Austin, 2016Austin, , 2017Waters, 2017;Austin and Nuño de la Rosa, 2018;Nicholson and Dupré, 2018;Laplane et al, 2019;Triviño, 2019). Concretely, we have shown how approaching the concept of holobiont adaptation by appealing to the notions of emergence and inter-identity allows to shed light on some of the perceived issues in contemporary hologenome literature.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, what requires explanation is robustness itself and "to account for robustness is to account for multiple realizability" (Austin 2016: 656; emphasis in the original). Thus, and to briefly respond to an objection raised by an anonymous reviewer, we believe that it remains to be shown that 'realization' and 'multiple realization' have managed to go beyond their mere descriptive function, including in those cases in which those terms are used in connection with the phenomena of concern to eco-evo-devo, as, for example, in Austin (2016) or in Love (2018). Neither Austin nor Love provide any indication of what they mean by 'realization', whether it is R F , R D or something entirely different, and until this is clarified, we can only reaffirm our suspicion that, as the key concepts of eco-evodevo find better and better explanations, 'realization' and 'multiple realization' will eventually be explained away.…”
Section: Conclusion: What All This Points Tomentioning
confidence: 98%
“…In this paper, I shall not directly argue for this claim even though it is not (yet) a popular one and has been met with explicit criticism in the mechanistic camp of philosophers of biology (Austin 2016). Assuming that some version of process ontology is indeed appropriate for biology, I shall instead address the question of whether the process ontological turn envisaged for biology and the philosophy of biology is actually compatible with the appeal to biological autonomy and autopoiesis common among the supporters of the non-reductionist stream of the systems biological turn.…”
Section: Introductionmentioning
confidence: 93%